The Impact of the Tourism Sector, Transportation Infrastructure, Number of Workers, and Hotel Occupancy Rates on the Regional Economy in Yogyakarta Province - Dhiya Rana Hafizhah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study analyzes the economic dynamics and development of the tourism sector in the Special Region of Yogyakarta (DIY) Province during the 2015–2024 period. The research employs a quantitative descriptive approach using secondary data obtained from the Central Bureau of Statistics (BPS). Data analysis is carried out through descriptive statistical methods and trend analysis to capture changes and patterns over time. The variables examined include regional economic growth, the number of tourist visits, road infrastructure development, labor absorption, and hotel occupancy rates across five districts/cities in the province. The findings indicate that the economy of DIY demonstrates relatively strong resilience in the post-COVID-19 pandemic period, supported by gradual recovery in tourism-related activities. The development and operation of Yogyakarta International Airport have significantly contributed to economic growth in Kulon Progo Regency, particularly by improving accessibility and investment opportunities. The tourism sector continues to serve as the main economic driver in the region, with tourist visits largely concentrated in Sleman Regency and Yogyakarta City, while Gunungkidul Regency shows considerable potential for nature-based tourism development. Overall, the study concludes that equitable infrastructure development and the strengthening of the service sector are crucial to ensuring sustainable and inclusive economic growth in the Special Region of Yogyakarta.